EXPLANATION OF DISCOURSE MARKERS (Spectrum Journal of Innovation, Reforms and Development, 2023)
A heterogeneous functional class comprising a variety of grammatical categories united by a shared goal is known as discourse markers. Discourse markers ensure the coherence of the text by simplifying the transition between textual elements and connecting them. Additionally, discourse markers highlight the semantic-pragmatic links that exist between the textual fragments they link.